(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
The article proposes hydrodynamic models describing the interaction between surface water and groundwater under furrow irrigation of cotton. These models allow for characterization of filtration processes and surface runoff at various levels of detail and accuracy. Based on mass-transfer models of the interaction between filtration and surface flows, the processes of water movement in the furrow, infiltration flow within the aeration zone, and variations in the groundwater level within the saturated zone were investigated.